Czech Republic, Republic of Estonia, Hungary, Republic of Latvia, Republic of Lithuania, Republic of Poland, Slovak Republic, and Republic of Slovenia : Export Structure and Credit Growth. (IMF Staff Country Reports; Country Report ;, 2006)
Of the new members entering the European Union (EU) in May 2004, several had achieved a decade of impressive export growth, expanding significantly their shares of world markets. The empirical analysis shows that over the period 1994-2004, quality and technology upgrading associated with the structural transformation were, indeed, also associated with increased market share. Several bivariate relationships to motivate an empirical framework for analyzing the evolution of market shares are ascribed. It gives the basic regressions explaining the changes in market shares for 58 countries.